2016
DOI: 10.1038/nn.4378
|View full text |Cite
|
Sign up to set email alerts
|

Evolving insights into RNA modifications and their functional diversity in the brain

Abstract: In this Perspective, we expand the notion of temporal regulation of RNA in the brain and propose that the qualitative nature of RNA and its metabolism, together with RNA abundance, are essential for the molecular mechanisms underlying experience-dependent plasticity. We discuss emerging concepts in the newly burgeoning field of epitranscriptomics, which are predicted to be heavily involved in cognitive function. These include activity-induced RNA modifications, RNA editing, dynamic changes in the secondary str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
65
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(67 citation statements)
references
References 85 publications
1
65
1
Order By: Relevance
“…A large variety of studies have shown that the activity ADARs (adenosine deaminases acting on RNAs), responsible for A-to-I editing, are highly expressed in nervous systems (Picardi et al 2015), and markedly increased during primate evolution (Paz-Yaacov et al 2010). These modifications do not only affect protein-coding genes, but also noncoding transcripts, and thus may be central to learning and plasticity in brain function (Lence et al 2016;Nainar et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…A large variety of studies have shown that the activity ADARs (adenosine deaminases acting on RNAs), responsible for A-to-I editing, are highly expressed in nervous systems (Picardi et al 2015), and markedly increased during primate evolution (Paz-Yaacov et al 2010). These modifications do not only affect protein-coding genes, but also noncoding transcripts, and thus may be central to learning and plasticity in brain function (Lence et al 2016;Nainar et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, our findings are not only applicable to RNA structure, but also to the field of RNA modifications. RNA modifications are known to alter the structure, function and activity of RNA molecules [42][43][44][45][46][47][48] . Recent papers have analyzed multiple RNA-Seq datasets looking for mismatched nucleotide signatures, finding that many RNA sequences contain modified nucleosides, 29,30,49 , and in the last year, genome-wide maps identifying thousands of m 1 A modifications have been made available 50 .…”
Section: Discussionmentioning
confidence: 99%
“…S1A-C.). However, the level of mRNA expression does not necessarily reflect the functional relevance of a given gene (25). Given previous findings of a role for Gadd45β in regulating contextual fear memory, we therefore designed shRNAs against all three members of the Gadd45 family according to established protocols (26), and validated these in vitro (SI Appendix Fig.…”
Section: Resultsmentioning
confidence: 99%